Teachers' Efforts to Improve the Speaking Skills of Grade IV Students in Indonesian Learning at SD-IT Teuku Umar - Asfi Mujiati (Darul Ilmi Bina Insan Foundation, 2023)
In language learning there are four components, namely: 1) Indonesian skills, 2) knowledge of Indonesian, and 3) literary appreciation. Furthermore, Indonesian skills are further divided into 4 aspects, namely (1) listening, (2) speaking, (3) reading, and (4) writing. This article aims to examine more deeply about how teachers' efforts in improving speaking skills at SD IT Teuku Umar Meulaboh. The formulation of this research problem is what is meant by speaking skills and what efforts teachers make in improving speaking skills at Teuku Umar Meulaboh IT Elementary School. In this research, researchers used qualitative research methods. By collecting data using three ways, namely, Interview, Observation, Documentation. In general, methods that can be used in improving students' speaking skills are role-playing methods, storytelling methods, mind mapping methods, group discussion methods, and show and tell methods. The main purpose of speaking is as a communication tool to convey ideas, ideas, thoughts. The purpose of speaking is very important, where speaking is a guideline for speakers in building and conveying ideas for a particular talk.